Challenge-based learning: A ‘entrepreneurship-oriented’ teaching experience (2020)
Challenge-based Learning (CBL) is a pedagogical approach that actively involves students in a realistic, problematic and meaningful situation related to their environment, which requires defining a challenge and implementing a solution for it (OIETM, 2015). The CBL methodology was applied by instructors with the support of students, part of the management programme from a Colombian university. The goal was to assess the validity of the methodology and examine solutions proposed by students to real-life problems in organisations. After assessing the challenge-based learning (CBL) it can be concluded, that a link to the entrepreneurial orientation exists. This link promotes the development of critical and constructive thinking, while encouraging students to analyse, design, develop and execute solutions for real-life problems, similar to those they will encounter as graduate students in any organisation. © 2020 British Educational Leadership, Management & Administration Society (BELMAS).